Paid Board Prototype With Monitoring Google Sheet - Rakhmad Fajar Ashari; Indah Sulistiyowati; Akhmad Ahfas; Arief Wisaksono (Procedia of Engineering and Life Science, 2022)
Many people prefer the money deposit box as a method of money storage even if there are many different types of useful places to do so. As a result, a Banknote Piggy Bank Prototype with Google Sheet Monitoring was created. a device that provides data on the amount of money saved. to use RFID as an access tool to scan ID cards. Three ID cards are included with this tool: a savings ID card, an unregistered ID card, and an ID card that may be used to withdraw money from savings accounts. The TCS34725 sensor is used in the design to read the money's nominal value and detect color. 20X4 LCD is being used as a display. can use a Wemos d1 small to monitor data after it has been saved and shown in a Google SpreadSheet. The piggy bank door lock employs a Servo Motor SG 90 for media, a Relay to start the motor, and an RTC Ds1307 to display the time and date. For use as a method of lowering the voltage in the system circuit is the LM2596 Regulator module. While the entire system needs an Arduino Microcontroller to be controlled.